Assessing the Post-Vaccination Impact of Different Brands of COVID-19 Vaccines in Bangladeshi Population (Faridpur Medical College Journal, 2025)
The Covishield was the first vaccine introduced in Bangladesh to combat the global COVID-19 pandemic. Gradually, Bangladesh introduced Moderna, Sinopharm, and Pfizer-BioNTech vaccines to combat COVID-19. The goal of this study was to assess the short- and long-term adverse effects of these vaccinations on the Bangladeshi people. A cross-sectional study was undertaken on social media and in face-to-face interviews with vaccinees. The collected data were then analyzed to assess the effectiveness and adverse effects of the vaccine after administration.This study garnered a total of 502 responses; the majority of respondents were between 18 and 40 years old, and 74.7% were male. Before vaccination, 13.94% of respondents were infected with the SARS-CoV-2 virus. From the populations under survey, 210 (after the 1st dose) and 222 (after the 2nd dose) reported various side effects after taking the COVID-19 vaccine. Oxford-AstraZeneca, Sinopharm, and Pfizer-BioNTech showed relatively fewer post-vaccination complications. A total of 34.06% of those who received the COVID-19 vaccine reported experiencing localized symptoms, the most prevalent of which were swelling and pain at the injection site following immunization. To assess the effectiveness of these vaccines, 47 participants were infected with COVID-19 after vaccination, but only four were hospitalized. Within 7 days of treatment, 61.7% of infected patients were recovered. However, to assess the long-term effects of post-vaccination, data on 273 individuals was collected separately after one year following the initial vaccination, and most of the respondent's results were similar to the initial study.Faridpur Med. Coll. J. 2025;20(1): 29-35